Fractional order PID controlled hybrid Cuk converter for electric vehicle - Bhavani, Nallamilli P. G.; Raj, S. Dinakar; Sujatha, K.; Navaprakash, N.; Ezhilarasan, D. (International Journal of Applied Power Engineering (IJAPE), 2025)
Choosing the right controller with the right approach is one of any power converter's biggest concerns. In order to optimise induction heating, a hybrid Cuk converter with a fractional-order proportional integral derivative (FOPID) controller is built. The findings show an improved time domain responsiveness in the FOPID controlled closed-loop hybrid DC-DC converter (CDHC) system. In order to improve the interface between the resonant inverter and DC source and to step up voltage with less output ripple, Cuk converters are used. The research project is concerned with modelling and simulating a hybrid closed-loop DC converter system. The findings show an improved time domain responsiveness in the FOPID controlled CDHC system. The suggested approach offers advantages such as high-power density and buck boost capability. After being inverted, the Cuk converter's output is applied to a DC load. The time responses of the closed loop proportional integral (PI) and FOPID controlled homogeneous charge compression ignition (HCCI) systems are compared. The hardware is implemented and tested for the CDHC system for electric vehicles. The results indicate that the FOPID controlled CDHC system has enhanced time response and benefits such as high-power density buck boost ability.